International standards in the fight against terrorism - Janković Dijana (Međunarodni Problemi, 2010)
Terrorism as a phenomenon of the modern society threatens to jeopardize the most important achievements of the modern society. The international community devotes much attention to the fight against terrorism and a number of legal instruments and standards that illustrate the basic message have been formulated in international documents - and the message is that it is possible to fight against terrorism effectively only if principal standards of internationally protected human rights are fulfilled. The fight against terrorism must never lead to the abolition of values and freedoms that are imperiled by terrorist acts. Even if the need to impose certain restrictions for protection of legitimate interests arouses they must be controlled, while they should protect basic human rights and freedoms. Regulating formal conditions for human rights limitation is the way to control the fight against terrorism and prevent the unlimited space for violation of the established and guaranteed freedom standards. The paper refers to the provisions of the European Convention on Human Rights and Fundamental Freedoms and the International Covenant on Civil and Political Rights, which provide some limitations to the guaranteed human rights as well as the limitation to their usage also exploring to what extent these restrictions are applied in the fight against terrorism.